Folding Under Pressure or Rising to the Occasion? Perceived Time Pressure and the Moderating Role of Team Temporal Leadership - Maruping, Likoebe M.; Venkatesh, Viswanath; Thatcher, Sherry M. B.; Patel, Pankaj C. (Academy of Management Journal, 2015)
“Team temporal leadership” orients teams toward managing the time-related aspects of their work. We examine how perceived time pressure affects team processes and subsequent performance under weak versus strong team temporal leadership. The results of our field study of 111 project teams show that the mediated relationship between perceived time pressure and team performance is non-linear. Moreover, this non-linear mediated relationship is moderated by team temporal leadership such that, under strong team temporal leadership, the indirect effect of perceived time pressure on team performance is mostly positive, while, under conditions of weak team temporal leadership, the indirect effect is positive at low levels of perceived time pressure and negative at intermediate to high levels. Implications for current and future time pressure research are also discussed.